Synaptotagmin‐11 inhibits cytokine secretion and phagocytosis in microglia. Issue 10 (7th July 2017) - Du, Cuilian; Wang, Yalong; Zhang, Feifan; Yan, Shuxin; Guan, Yuan; Gong, Xiaoli; Zhang, Ting; Cui, Xiuyu; Wang, Xiaomin; Zhang, Claire Xi
Abstract: Cytokine secretion and phagocytosis are key functions of activated microglia. However, the molecular mechanisms underlying their regulation in microglia remain largely unknown. Here, we report that synaptotagmin‐11 (Syt11), a non‐Ca 2+ ‐binding Syt implicated in Parkinson disease and schizophrenia, inhibits cytokine secretion and phagocytosis in microglia. We found Syt11 expression in microglia in brain slices and primary microglia. Interestingly, Syt11‐knockdown (KD) increased cytokine secretion and NO release in primary microglia both in the absence and presence of lipopolysaccharide. NF‐κB was activated in untreated KD microglia together with enhanced synthesis of IL‐6, TNF‐α, IL‐1β, and iNOS. When the release capacity was assessed by the ratio of extracellular to intracellular levels, only the IL‐6 and TNF‐α secretion capacity was increased in Syt11‐KD cells, suggesting that Syt11 specifically regulates conventional secretion. Consistently, Syt11 localized to the trans‐Golgi network and recycling endosomes. In addition, Syt11 was recruited to phagosomes and its deficiency enhanced microglial phagocytosis. All the KD phenotypes were rescued by expression of an shRNA‐resistant Syt11, while overexpression of Syt11 suppressed cytokine secretion and phagocytosis. Importantly, Syt11 also inhibited microglial phagocytosis of α‐synuclein fibrils, supporting its association with Parkinson disease. Taken together, we propose that Syt11 suppresses microglial activation under both physiological and pathological conditions through the inhibition of cytokine secretion and phagocytosis. Main Points: Syt11 specifically inhibits IL‐6 and TNF‐α secretion and NF‐κB activation in primary microglia. Syt11 inhibits phagocytosis in primary microglia.